Physical Activity Level, Smoking Habits, and Nicotine Dependence Among E-Cigarette Users in Medical Students of Tarumanagara University, Academic Year 2022–2023 - Susy Olivia; Muhammad Faqih (Pusat Riset dan Inovasi Nasional, 2025)
Medical students are vulnerable to unhealthy lifestyles, such as low physical activity and smoking habits, including the use of electronic cigarettes. This study aimed to determine the levels of physical activity, smoking habits, and nicotine dependence among medical students of Universitas Tarumanagara, class of 2022–2023. This research employed a cross-sectional design involving a total of 60 respondents. Physical activity was assessed using the IPAQ-SF, smoking habits with the Brinkman Index, and nicotine dependence with the PS-ECDI. The results showed that among the medical students of Universitas Tarumanagara, 59 students (98.3%) had low physical activity and 1 student (1.7%) had moderate physical activity. Based on the Brinkman Index, 29 students (96.7%) were categorized as light smokers and 1 student (3.3%) as a moderate smoker. Of the 36 students who used electronic cigarettes, 1 student (2.8%) had low nicotine dependence, 7 students (19.4%) had moderate dependence, and 28 students (77.8%) had high dependence. In conclusion, 98.3% of students had low physical activity, 96.7% were light smokers, and 77.8% of e-cigarette users had high nicotine dependence.